2021
DOI: 10.1080/16583655.2021.1886418
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic intoxication tool for clozapine and phenytoin using hybrid micelle liquid chromatography

Abstract: Micellar liquid chromatography was employed for the quantification and separation of the antidepressant drug clozapine (CLZ) and antiepileptic agent phenytoin (PHY). This mixture was separated using C8 column operating at 40°C using a mobile phase consisting of 0.075 M sodium dodecyl sulphate (SDS), 10% acetonitrile, 0.3% triethylamine (TEA), adjusted to pH 2.5 by 2 M ortho-phosphoric acid and applying a simple gradient program starting with a flow rate of 0.8 mL/min for the first 10 min of analysis applying 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…160 A micellar liquid chromatographic technique done on antipsychotic clozapine in vivo is a suggested diagnostic tool for intoxication with other drugs in the emergency management of schizophrenia. 161 Improved permeability, dissolution and bioavailability of micelles loaded with aripiprazole is evaluated in vitro and in vivo by Vieri Piazzini et al in the management of schizophrenia. 162 Another study conducted by Singla P. et al reveals that sustained release of drug action is observed on solubilising the hydrophobic drugs clozapine and oxcarbazepine in different molecular weight pluronic mixed micelles in vitro and in vivo.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…160 A micellar liquid chromatographic technique done on antipsychotic clozapine in vivo is a suggested diagnostic tool for intoxication with other drugs in the emergency management of schizophrenia. 161 Improved permeability, dissolution and bioavailability of micelles loaded with aripiprazole is evaluated in vitro and in vivo by Vieri Piazzini et al in the management of schizophrenia. 162 Another study conducted by Singla P. et al reveals that sustained release of drug action is observed on solubilising the hydrophobic drugs clozapine and oxcarbazepine in different molecular weight pluronic mixed micelles in vitro and in vivo.…”
Section: Accepted Manuscriptmentioning
confidence: 99%